TEAM ASSISTED INDIVIDUALIZATION BERBASIS PENYELESAIAN MASALAH: METODE BARU DALAM PEMBELAJARAN TEORI EKONOMI MIKRO - Hidayat, Taufiq; Astuti, Rika Pristian Fitri (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2018)
The aims of this research were to develop, implement, and evaluate the problem solving based-learning method of Team Assisted Individualization (TAI). This learning method was designed to encourage studentâ€™s involvement during the learning process, provide students challenges to have High Order Thinking students, and ease them to understand the gist of externality material on the course of micro economics theory.Â Â This research was conducted at a private university in Indonesia. Its results demonstrated that the students, in general, gave positive responses during the implementation of problem solving-based of TAI method. They also argued that this method was beneficial for them. In conclusion, TAI method with problem solving base could be considered by lecturers to be employed for learning micro economics in the future.